PENGEMBANGAN VIDEO PEMBELAJARAN BIOLOGI BERBASIS DISCOVERY LEARNING SMA NEGERI 1 MORO’O - GULO, REMILIANTI; WARUWU, TOROZIDUHU; ZEGA, NOVELINA ANDRIANI; GULO, HARDIKUPATU (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This research is based on the problem of students' low level of understanding in mastering the material. To overcome this, research was conducted using video teaching materials based on Discovery Learning at SMA Negeri 1 Moro'o so that it was feasible, practical and effective. This type of research is development (Research and Development). The development model used is a 4D model which consists of four stages, namely Define, Design, Develop and Disseminate. Discovery Learning-based biology learning videos developed through validity testing stages by four validators (material experts, GMP material experts, language experts, and media experts), individual tests, small group tests, and field tests conducted in class XI-Mia-1 SMA Negeri 1 Moro'o has been tested as valid and appropriate by material expert validators in revision III 90%, GMP material expert validators in revision I 95%, language expert validators in revision II 97%, and media expert validators in revision I 95% . The practicality of the video in individual trials was 87%, in small group trials was 92% and in field trials was 90% with very practical criteria. The effectiveness of the video has also been tested in the very effective category with a classical completion percentage reaching 91%. Based on the research results above, Discovery Learning-based videos in biology subjects in class XI-Mia-1 SMA Negeri 1 Moro'o which have been developed using the 4D model have met the requirements and are suitable for use. ABSTRAKPenelitian ini didasarkan pada permasalahan rendahnya tingkat pemahaman peserta didik dalam penguasaan materi. Untuk mengatasi hal tersebut, dilakukan penelitian dengan menggunakan bahan ajar video berbasis Discovery Learning SMA Negeri 1 Moro’o sehingga layak, praktis, dan efektif. Jenis penelitian ini adalah pengembangan (Research and Development). Model pengembangan yang digunakan adalah model 4D yang terdiri dari empat tahap yaitu Define (Pendefenisian), Design (Perancangan), Develop (Pengembangan) dan Disseminate (Penyebaran). Video pembelajaran biologi berbasis Discovery Learning yangdikembangkan melalui tahap uji validitas oleh empat validator (ahli materi, ahli materi GMP, ahli bahasa, dan ahli media), uji perorangan, uji kelompok kecil, dan uji lapangan yang dilakukan di kelas XI-Mia-1 SMA Negeri 1 Moro’o telah teruji valid dan layak oleh validator ahli materi pada revisi III 90%, validator ahli materi GMP pada revisi pada revisi I 95%, validator ahli bahasa pada revisi II 97%, dan validator ahli media pada revisi I 95%. Kepraktisan video pada uji coba perorangan sebesar 87%, uji kelompok kecil sebesar 92% dan uji lapangan sebesar 90% dengan kriteria sangat praktis. Efektifitas video juga telah teruji kategori sangat efektif dengan persentase ketuntasan klasikal mencapai 91%. Berdasarkan hasil penelitian di atas, maka video berbasis Discovery Learning pada mata pelajaran biologi di kelas XI-Mia-1 SMA Negeri 1 Moro’o yang telah dikembangkan dengan model 4D telah memenuhi syarat dan layak untuk digunakan.